A poly(carbazole‐alt‐fluorene) π‐conjugated polymer bearing thiophenyl benzimidazole: synthesis, characterization and fluorescence recognition of metal ions and cysteine. Issue 11 (22nd June 2021) - Liu, Kuan; Wei, Yuhan; Xu, Jinyao; Qiu, Lingfei; Hu, Shaping; Wan, Jiayi; Feng, Juhua
Abstract: A novel conjugated polymer PFCZ‐IM containing 2‐(thiophen‐2‐yl)‐1H‐benzo[d]imidazole units was synthesized and characterized. The basic photophysical properties of the polymer and its fluorescence recognition behaviors toward metal ions and amino acids were investigated. In the study of the response of metal ions, PFCZ‐IM had high sensitivity to Fe 3+, Ag + and Cu 2+, which significantly quenched the fluorescence of the polymer. The binding of the 2‐(thiophen‐2‐yl)‐1H‐benzo[d]imidazole moiety to Cu 2+ was investigated by density functional theory calculation. Interestingly, [PFCZ‐IM‐Cu 2+ ] also exhibited outstanding characteristics of fluorescence 'turn on' in the presence of cysteine (Cys), as the interaction between Cu 2+ and Cys caused the polymer to dissociate from the complex. In particular, addition of 30 μmol L –1 of Cys can increase the Cu 2+ ‐quenching fluorescence of PFCZ‐IM by 34.8 times with short response time, demonstrating that [PFCZ‐IM‐Cu 2+ ] has tremendous potential in the actual detection of Cys. This polymer is expected to be utilized for dual fluorescence detection of specific metal ions and Cys. © 2021 Society of Industrial Chemistry. Abstract : The fluorescence of PFCZ‐IM is quenched in the presence of Cu 2+, Ag + and Fe 3+, while the addition of cysteine significantly recovers the fluorescence of the [PFCZ‐IM‐Cu 2+ ] complex system.